HUBUNGAN ANTARA SEKS PRANIKAH DENGAN PERILAKU SEKS REMAJA PADA SMK KERABAT KITA BUMIAYU KABUPATEN BREBES - Anggraeni, Nely; Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
The attitude is a predisposition to perform or not perform a certain behavior one sexual behavior. Having sex outside of marriage shows no sense of responsibility and raises a series of new problems that cause unwanted pregnancies, PMS, and HIV / AIDS.Simak Baca secara fonetik This study aimed to analyze the relationship between adolescent attitudes toward premarital sex with teen sexual behavior in SMK Relatives We Bumiayu Brebes District.This Reasearch clasified as analitycal researched with cross sectional plan. Population in this research is the students of SMK Kerabat Kita, consist of 822 students. This research use the sample of 89 respondent with cluster random sampling technique and also to  Analyze data use with univariat and bivariat analysis (Chi- Square test). The behavior of adolescent student toward sexual activity before getting married in SMK Kerabat Kita Bumiayu Kabupaten Brebes assesed that most respondent have bad behavior toward sexual activity before getting married. It consist in percentage 31 respondents (34,8 %) and the other that show better behavior consist of 25 respondents (28,1%). Sexual behavior of adolescent of student toward sexual activity before getting married consist that the most of them have risk sexual behavior that consist of  48 respondents (53,9%) and the others  have unrisk sexual behavior about 41 respondents(46,1%). Those datas show that there is a significant connection  between behavior of adolescent student toward sexual activity before getting married in SMK Kerabat Kita Bumiayu Brebes district 2010 with grade Chi-Square and counted about 47,229 with p 0,000.The relationship attitudes toward premarital sex with  adolescent sexual behavior teen in smk kerabat kita bumiayu brebes district  in 2010 are significant.For SMK should improve is related to religious activities associated with adolescent reproductive health in an integrated.   Key words: Adolescent’s behavior, sexual activity before getting married, and sexual behavior.